2019
DOI: 10.1055/s-0040-1709966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rocuronium and Vecuronium in Patients Undergoing Elective Ultrafast-Track Off-Pump Coronary Artery Bypass Surgery

Abstract: Background Neuromuscular blocking drugs are necessary in cardiac surgery to facilitate smooth intubation and ventilation conditions, avoid patient movement, reduce oxygen consumption, and prevent shivering. Hemodynamic stability is very essential in cardiac surgery because the coronary reserve is below normal in such patients. Aims This study was conducted with the objective of comparing rocuronium, the “near-ideal” muscle relaxant with vecuronium, an already established neuromuscular blocking agent in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The hemodynamic changes during intubation were comparable in a study by Mohamed and Sameh[ 12 ] study where vecuronium and rocuronium were used for rapid sequence induction in morbidly obese patients in a randomized study. Shah and Kulshrestha[ 13 ] also shown that in patients undergoing elective ultrafast-track off-pump coronary artery bypass graft, rocuronium provides good-to-excellent intubating conditions without any significant hemodynamic instability when compared with vecuronium which corroborated with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…The hemodynamic changes during intubation were comparable in a study by Mohamed and Sameh[ 12 ] study where vecuronium and rocuronium were used for rapid sequence induction in morbidly obese patients in a randomized study. Shah and Kulshrestha[ 13 ] also shown that in patients undergoing elective ultrafast-track off-pump coronary artery bypass graft, rocuronium provides good-to-excellent intubating conditions without any significant hemodynamic instability when compared with vecuronium which corroborated with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, any agent that stimulates the cardiovascular system and increases the myocardial oxygen demand should be avoided. 11 Vecuronium and rocuronium decrease the heart rate and are useful NMBs in patients with high baseline heart rate. 12 A recent study showed that vecuronium had better and more cardiac favourable variables and more cardiovascular stability than rocuronium and atracurium.…”
Section: Discussionmentioning
confidence: 99%
“…The anesthetic approaches that have been developed and utilized over period of time for patients undergoing OPCAB are general anesthesia (GA) with opioids and inhalation anesthesia; GA combined with controlled ventilation and HTEA; GA combined with intrathecal opioids; awake regional anesthesia with spontaneous ventilation using HTEA alone; total intravenous anesthesia (TIVA) with ETT; and TIVA with laryngeal mask airway (LMA). [3][4][5][6][7] Scientific evidence and practical experience make TIVA the recommended choice for cardiac surgery (►Fig. 1).…”
Section: Anesthetic Approaches In Opcabmentioning
confidence: 99%